Association of birth weight with body mass index of school children of central India: a cross sectional study - Petkar, Prithvi B.; Thakre, Sushama S.; Thakre, Subhash B.; Patil, Chaitanya R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Overweight and obesity has become an important public health problem in both developed and developing nations. This is even more alarming as obese children are likely to become obese adults. Methods: A cross sectional study was conducted in a government aided school in urban area of Nagpur, Maharashtra during January 2016 to April 2016. This study was conducted in students of age group of 9 to 15 years to assess the association of birth weight and body mass index of school children. Height and weight of the children were measured according to standard guidelines. BMI was calculated and classified using the percentile charts according to age and gender. Data was collected using EPI Info version 7.2. Descriptive statistics using frequencies and percentages were used. Chi square test was used to indicate the differences between two proportions. Odds ratio was used to define the strength of the association. Results: The mean age of children was 11.92±1.27 and 11.31±1.27 in males and females respectively. In our study, there was a significant positive association between the birth weight and body mass index of the children. Conclusions: We found that the children whose birth weight was lower than 2500 grams were having decreased risk of being overweight/ obese in their later life with an odds ratio of 0.55 (0.34 to 0.90). But, the correlation between the birth weight and body mass index is weakly positive (r=0.063).